P59 Systematic review and meta-analysis of early transjugular intrahepatic portosystemic stent-shunt (TIPSS) in the management of acute variceal bleeding. (28th September 2020) - Tripathi, Dhiraj; O'Neill, Frank; Patch, David; Joseph, Andrew; Aithal, Guru
Abstract : Introduction: Transjugular intrahepatic portosystemic stent-shunt (TIPSS) insertion is well established as an effective treatment for the management of bleeding in patients with decompensated cirrhosis. Current evidence suggests that early TIPSS (within 72 hours of a variceal bleed) using the GORE® VIATORR® stent effectively reduces portal pressure and improves prognosis in comparison to endoscopic band ligation (EBL) and medical management. We conducted a meta-analysis of trials comparing early TIPSS with EBL in cirrhotic patients with acute variceal bleeding. Methods: Systematic literature searches were conducted in MEDLINE, PubMed, EMBASE and Cochrane. Eligible studies were published between May 1999 and May 2020. The outcomes of interest were survival, re-bleeding and rate of hepatic encephalopathy. Risk Ratio (RR) estimates with 95% confidence interval (CI) were calculated using a random effects model and trials were evaluated using the Cochrane tool for the assessment of the risk of bias. Results: 8, 123 studies were identified by the search and three prospective controlled trials including 152 patients were included in the meta-analysis. Meta-analyses demonstrated that GORE® VIATORR® consistently and significantly reduced incidence of bleeding (RR = 0.20, 95% CI = 0.09–0.42, p = <0.001) (figure 1 ). This was associated an improvement in overall survival, which did not quite reach statistical significance, at 1 and 2 years (RR = 0.62, 95% CI = 0.33–1.19 and RR = 0.62, p = 0.16 95% CI = 0.31–1.26, p = 0.19). Incidence of hepatic encephalopathy was similar across the studies (RR = 1.01, 95% CI = 0.70–1.46, p = 0.97). Conclusion: TIPSS is more effective in preventing variceal re-bleeding than EBL and medical management, without an increase adverse events. While this was not associated with a statistically significant improvement in survival, it is likely that these findings were underpowered. High quality, adequately powered and multi-centre randomized trials evaluating clinical and quality of life outcomes are required to verify these results and inform robust economic evaluations of TIPSS in the management of variceal bleeding in patients with cirrhosis.